Assessing Ecosystem Health: An Analysis of Tourism related Change and Impact in Khumbu Valley, Nepal - Caravello, G. U.; Boselli, A. M.; Bertollo, P.; Baroni, A. (Ecoprint: An International Journal of Ecology, 2016)
Available with fulltext. Key words: Sagarmatha National Park; Tourism; Water quality; Biotic index; Human health Ecoprint An International Journal of Ecology Vol. 14, 2007 Page:45-64 Uploaded date: 31 May, 2011